RARE-18. GENETIC EVALUATION IN PATIENTS WITH CHOROID PLEXUS TUMORS. (4th December 2020) - Oliveira, Milena; Silva, Nasjla; Cappellano, Andrea; Almeida, Daniela; Cavalheiro, Sergio; Dastoli, Patrícia; Silva, Frederico; Lima, Fernanda
Abstract: INTRODUCTION: Choroid plexus tumors (CPT) are rare intraventricular neoplasms of epithelial origin. They usually occur in the 2nd year of life, corresponding to 0.4–0.6% of intracranial tumors in this age group. They are sub classified, according to WHO 2016, in choroid plexus carcinoma (CPC), atypical choroid plexus papilloma (ACPP) and choroid plexus papilloma (CPP). Li-Fraumeni syndrome (LFS) is present in 50% of patients with CPC. In Brazil, the TP53 p.R337H mutation affects 0.3% of the population in the South/Southeast. OBJECTIVE: Evaluate the incidence of genetic mutations in patients with choroid plexus tumors and therefore the importance of genetic evaluation. PATIENTS AND METHODS: Between 1992–2019, 38 patients were diagnosed with CPT in our institution, 23 with CPC. From 2012, 21 patients were referred for genetic evaluation, 16 of which had CPC (2 had previously CPP). Positive family history for neoplasms was present in 87.5%; 37.5% compatible with LFS, 50% of them with mutations. All the patients with positive, but unspecific, family history of neoplasms, had pathogenic mutation. The molecular investigation of the TP53 gene in patients with CPC was performed and positive in 56.2%: R337H (5 patients), R110C, R158H, H179R, R196* (1 patient each). Of those with R337H, p53 protein immunohistochemistry resulted in 90–100% positivity. One of the patients with CPP that evolved to CCP had the H179R mutation. Clinical course was similar among them, and with those without mutations. CONCLUSION: These results confirm the need for genetic evaluation in patients with choroid plexus tumors for adequate therapeutic management and long-term follow-up.